Sheep and goat farming in Los Pedroches (province of Córdoba, Spain) in the context of sustainable development - Luque-Revuelto, Ricardo Manuel; Moreno-Muñoz, Daniel; Giménez-García, Rubén (Revista de Estudios Andaluces, 2024)
Los Pedroches is one of the main Andalusian regions in sheep and goat production, although this sector, which has an extensive implantation and a long historical trajectory, has been affected by the agricultural crisis and the crisis in rural areas. The aim is to characterize, by means of different geographical analysis techniques, the current situation of the sheep and goat herd in Los Pedroches, and to assess its importance as a model of sustainable economic action in Sierra Morena in the face of depopulation and the rural crisis. Among the results obtained, it is concluded that it could be a key sector in this region from the point of view of the agri-food industry and commerce, and even from the consideration of new emerging activities such as rural tourism and the valorization and management of the cultural and natural heritage.